Micronutrient composition and acceptability of Moringa oleifera leaf‐fortified dishes by children in Ada‐East district, Ghana. Issue 2 (5th July 2016) - Glover‐Amengor, Mary; Aryeetey, Richmond; Afari, Edwin; Nyarko, Alexander
Abstract: Moringa oleifera (M. oleifera), a green leafy vegetable, is a good source of minerals and vitamins which could be consumed as part of diet to improve human health and well‐being. Drying M. oleifera leaves could make it readily available for use as a food fortificant. The objectives of the study were to determine micromineral and β ‐carotene content of dried M. oleifera leaves, and leaf‐incorporated local dishes, and also assess school children's (4‐12 yr) acceptability of dried M. oleifera leaf‐incorporated local dishes and feasibility of introducing dried leaves into a school lunch menu. M. oleifera leaves were solar dried, milled into powder, and packaged into polythene bags. Moisture level in the dried leaves and pH were determined. Minerals in the leaf powder were determined by Atomic Absorption Spectrophotometry (AAS). Beta‐carotene levels were determined by spectrophotometry. Acceptability tests of dishes fortified with M. oleifera leaf powder were conducted with score sheets (Smileys) on a 5‐point hedonic scale of "Like Extremely" to "Dislike Extremely", and dishes ranked to determine preference. Dried M. oleifera leaves contained high levels of micronutrients: 0.36 ± 0.04 mg/100 g Copper (Cu); 5.80 ± 0.68 mg/100 g Manganese (Mn); 20.96 ± 1.37 mg/100 g Iron (Fe); 6.79 ± 1.82 mg/100 g Zn; and 21.42 ± 1.67 mg/100 g β ‐carotene. The dishes showed significant levels of these minerals compared to the nonfortified dishes ( P < 0.05). M. oleifera leaf‐fortified dishes were also highly acceptable to the children (highest mean score of 5.0 ± 0 of 5 and lowest of 3.50 ± 1.43 of 5). M. oleifera leaf powder contains high levels of the micronutrients β ‐carotene, Zn, Mn, and Fe, comparable to levels found in amaranth and spinach. M. oleifera leaf‐fortified local dishes were well accepted by children in Ada‐East district. M. oleifera leaf fortified dishes could be good sources of β ‐carotene and other minerals for children vulnerable to malnutrition in Ghana. Abstract : M. oleifera leaf powder contains significant levels of the micronutrients β ‐carotene, Cu, Zn, Mn, and Fe. M. oleifera leaf‐fortified local dishes were well accepted by children in Ada‐East district. M. oleifera leaf fortified dishes could be good sources of β ‐carotene and other minerals for children vulnerable to malnutrition in Ghana.